Analyzing English for Academic Purposes textbooks in China: A study of intercultural issues - Li, Yulong; Yao, Pengfei; Hu, Bo (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
An increase of English for Academic Purposes (EAP) teaching in China has resulted in a surge of EAP textbooks on the market. However, there has been little accompanying interest in how well intercultural issues are handled and presented in these publications. Accordingly, the present study employs Chinese students’ Cultures of Learning (CoL) and contrastive rhetoric (CR) as reflection points in the analysis of the content, production, and consumption of two series of EAP textbooks adapted from overseas textbooks. Findings revealed that intercultural differences are not given due recognition in the textbooks which in some cases can lead to confusion and misunderstanding. Meanwhile, the teachers involved in the study, as users of the other textbook series, were found to treat the textbooks only as a supplementary EAP teaching resource. Moreover, the continued confusion on the part of some of the students involved in the study highlighted the desirability for future textbooks to render intercultural differences in a critical EAP manner.